RNA interference therapeutics for cardiac regeneration. (October 2021) - Huntington, Josef; Pachauri, Manendra; Ali, Hashim; Giacca, Mauro
Abstract : There is an impelling need to develop new therapeutics for myocardial infarction and heart failure. A novel and exciting therapeutic possibility is to achieve cardiac regeneration through the stimulation of the endogenous capacity of cardiomyocytes to proliferate. Proof-of-concept evidence of microRNA-induced cardiac regeneration is available in both small and large animals using viral vectors. However, a clinically more applicable strategy is the development of lipid-mediated nanotechnologies for the administration of RNA therapeutics as synthetic molecules. The recent success of the Stable Nucleic Acid Lipid Particle (SNALP) platform for the generation of nanosized, efficient and non-inflammatory lipid nanoparticles paves the way to the development of injectable nanoformulations of microRNAs through cardiac catheterisation.